Analysis of Independent Study Length of UNIMED Science Education Students Intake of 2023 on GPA - Sitepu, Ade Prisma; Silaban, Awy; Sijabat, Dea Clara May Christin; Firmansyah, Ibnu; Kalsum, Ummi (CV. Rayyan Dwi Bharata, 2025)
This study aims to evaluate the self-directed learning profiles of 78 Science Education students from the 2023 cohort by analyzing 15 indicators of study habits, complemented by GPA data as a measure of academic performance. The findings indicate that students demonstrate a moderate level of self-directed learning ability, although its implementation remains inconsistent. Students generally engage in regular independent study and extend their study duration when academic performance declines. However, irregular adherence to study schedules, limited frequency of material review, and a tendency to reduce study time due to competing activities highlight suboptimal discipline and time management. Self-evaluation and long-term learning planning have also not been fully internalized. These patterns are reflected in GPA achievements that fall within the “good” category yet have not reached optimal levels. The study underscores the need for strengthened time-management strategies, habitual self-evaluation, and increased utilization of supplementary learning resources to support sustained academic improvement.